OER-based Online Micro-courses - Rory McGreal; Wayne Mackintosh; Dave Lane (Flexible Learning Association of New Zealand, 2023)
The OER Universitas (OERu) is a consortium of more than 30 higher education institutions on five continents. It was founded in 2011 to provide learners everywhere with learning opportunities and pathways to official recognition or credit. The OERu maintains a very economical base with very low expenses. It supports a sustainable learning environment with incremental increases in infrastructural capacity as and when it is needed. The OERu's global digital infrastructure has been created to facilitate learner access to micro-courses on the internet from any geographical location. This Next Generation Digital Learning Environment (NGDLE) is based entirely on free and open source software (FOSS). The OERu has established a working model for transnational micro-credentialling for approved university qualifications. To date it has supported more than 200,000 learners in over 100 countries. The OERu is based on a scalable, FOSS NGDLE which has dramatically reduced the cost of providing learning opportunities to anyone, anywhere, on the web.